Dabigatran Use Does Not Increase Intracranial Hemorrhage in Traumatic Geriatric Falls When Compared with Warfarin. Issue 10 (October 2015) - Pozzessere, Anthony; Grotts, Jonathan; Kaminski, Stephen
Patients on anticoagulation are at increased risk for intracranial hemorrhage (ICH) after trauma. This is important for geriatric trauma patients, who are increasing in number, frequently fall, and often take anticoagulants. This study sought to evaluate whether prehospital use of dabigatran, a newer anticoagulant, is associated with outcome differences in geriatric trauma patients suffering falls when compared with warfarin. The registry of a Level II community trauma center was used to identify 247 patients aged 65 and older who sustained a fall while taking prehospital dabigatran or warfarin admitted between December 2010 and March 2014. Patients on warfarin were included if their International Normalized Ratio was therapeutic (2–3). About 176 of the 247 patients were then compared using coarsened exact matching. In the matched analysis, overall population means for age, Glasgow Coma Score, and Injury Severity Score were 83.5, 14.7, and 5.1, respectively. The overall rate of ICH was 12.5 per cent, with a mortality rate of 16.1 per cent for patients who sustained an ICH. There were no observed differences in ICH, hospital length of stay, intensive care unit length of stay, or mortality between patients taking prehospital warfarin or dabigatran.